Pengaruh Work Environment Terhadap Job Satisfaction Dengan Work Relationship Sebagai Variabel Mediasi - Ratih Indriyani; Aksel Imanuel Iman (Majalah Ekonomi, 2021)
This study aims to see the effect of work environment on job satisfaction in financing company employees in Ambon city with work relationship as a mediating variable. This is a quantitative study, involving 100 employees of 5 finance companies in Ambon city as respondents. This study is using partial least square, results show that work environment and work relationships have a significant effect on job satisfaction and work environment has a significant effect on work relationships among finance company employees in Ambon city.